Fractional Order Sliding Mode Control of Linear Motor for Wood Cutting CNC Machine Tools Based on Particle Swarm Optimization - Lei Yang , Chuansheng Tang (Forest Chemicals Review)
In order to improve the control performance of the system and solve the problem of the lack of single control method of linear motor in wood cutting CNC machine tools, this paper combines fractional PID algorithm with sliding mode variable structure algorithm. In order to avoid the complexity and uncertainty of the parameters manually, particle swarm optimization is used to optimize the parameters of the sliding mode variable structure algorithm. In this paper, the sliding mode variable structure controller of fractional PID is optimized and improved to improve its control accuracy. This paper applies the new algorithm to the single-phase full bridge inverter of linear motor in wood cutting CNC machine tool. The simulation results are compared with the fractional PID sliding mode variable structure control function (PID SMC) and the sliding mode variable structure control (SMC) method. The results show that the particle swarm optimization algorithm can find the optimal solution in a short time because of its fast convergence rate. The static error of the algorithm is small and the rising speed is fast. The method makes the linear motor control system of CNC machine tool have strong ability of buffeting and strong robustness.